Direct binding to and tyrosine phosphorylation of the alpha subunit of the type I interferon receptor by p135tyk2 tyrosine kinase. - Colamonici, O (1994)
Binding of type I interferons (IFNs) to their receptors induces rapid tyrosine phosphorylation of multiple proteins, including the alpha and beta subunits of the receptor, the polypeptides that form the transcriptional activator ISGF3 alpha (Stat113, Stat84, and Stat91), and the p135tyk2 and Jak-1 tyrosine kinases. In this report, we demonstrate that the alpha subunit of the type I IFN receptor (IFN-R) corresponds to the product of a previously cloned receptor subunit cDNA and, further, that the p135tyk2 tyrosine kinase directly binds and tyrosine phosphorylates this receptor subunit. Glutathione S-transferase (GST) fusion proteins encoding the different regions of the cytoplasmic domain of the alpha subunit can bind the p135tyk2 contained in human cell lysates. The association between the alpha subunit and Tyk2 was demonstrated by immunoblotting with anti-Tyk2 and antiphosphotyrosine antibodies and by using an in vitro kinase assay. Analogous experiments were then performed with recombinant baculoviruses encoding constitutively active Jak family tyrosine kinases. In this case, p135tyk2, but not Jak-1 or Jak-2 protein, binds to the GST-IFN-R proteins, suggesting that the interaction between these two proteins is both direct and specific. We also demonstrate that Tyk2, from extracts of either IFN alpha-treated human cells or insect cells infected with the recombinant baculoviruses, can catalyze in vitro phosphorylation of GST-IFN-R protein in a specific manner. Deletion mutants of the GST-IFN-R protein were used to localize both the binding and tyrosine phosphorylation site(s) to a 46-amino-acid juxtamembrane region of the alpha subunit, which shows sequence homology to functionally similar regions of other cytokine receptor proteins. These data support the hypothesis that the Tyk2 protein functions as part of a receptor complex to initiate intracellular signaling in response to type I IFNs.